2004
DOI: 10.1104/pp.103.033969
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Physical Mapping in Pennisetum squamulatum Reveals Extensive Chromosomal Heteromorphism of the Genomic Region Associated with Apomixis

Abstract: Gametophytic apomixis is asexual reproduction as a consequence of parthenogenetic development of a chromosomally unreduced egg. The trait leads to the production of embryos with a maternal genotype, i.e. progeny are clones of the maternal plant. The application of the trait in agriculture could be a tremendous tool for crop improvement through conventional and nonconventional breeding methods. Unfortunately, there are no major crops that reproduce by apomixis, and interspecific hybridization with wild relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
81
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(87 citation statements)
references
References 58 publications
(50 reference statements)
4
81
0
Order By: Relevance
“…Recent results obtained for C. ciliaris seem to confirm this hypothesis since the apomixis locus of this species is located near the centromere in a heterochromatin-rich region (Akiyama et al 2005). Several characteristics associated with heterochromatin have been observed at the same locus of P. squamulatum, although it is not located close to the centromere (Akiyama et al 2004). In contrast to these results, the ACL of P. simplex appeared to be located in a heterochromatic-poor region further away from the centromere.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Recent results obtained for C. ciliaris seem to confirm this hypothesis since the apomixis locus of this species is located near the centromere in a heterochromatin-rich region (Akiyama et al 2005). Several characteristics associated with heterochromatin have been observed at the same locus of P. squamulatum, although it is not located close to the centromere (Akiyama et al 2004). In contrast to these results, the ACL of P. simplex appeared to be located in a heterochromatic-poor region further away from the centromere.…”
Section: Discussionmentioning
confidence: 69%
“…In a recent paper, Goel et al (2003) reported for the first time the FISH-aided localization of the apomixis locus on metaphase chromosomes and they claimed that its vicinity to the centromere in Cenchrus ciliaris and to centromeric repeats in P. squamulatum could cause the repression of recombination at the same locus in these species. Further FISH analyses on pachytene chromosome preparations of the same species are in favour of these assumptions (Akiyama et al 2004;Akiyama et al 2005;Ozias-Akins et al 2003). FISH using pachytene chromosomes as targets offers superior spatial resolution of adjacent probes compared to metaphase chromosomes and display clearly the dense heterochromatic regions on the chromosomes and so allow the assignment of a probe position in relation to the structural organization of its surrounding chromosome context (de Jong 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Since P. squamulatum is considered as a potential donor for desirable traits for pearl millet improvement, the prospects of utilization of hybrids is high, not only with respect to introgression of desirable traits, but also to understand complex traits such as perenniality and apomixis. Genetic analysis involving P. squamulatum (2nϭ54) cytotypes revealed apomixis (apospory) under control of a complex locus designated as ASGR (Apospory Specific Genomic Region), localized on a single squamulatum chromosome, and characterized by hemizygosity and suppressed recombination (Ozias-Akins et al 2003, Akiyama et al 2006. Similar analyses involving 2nϭ56 cytotype shall be important to identify the presence of same or different phenomenon as in 2nϭ54 cytotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, genomic studies on gametophytic apomixis have been performed in some plant species, such as in Pennisetum and Cenchrus using genetic markers and bacterial artificial chromosome (BAC) clones linked to the apomixis locus (Akiyama et al, 2004;Goel et al, 2006;Gualtieri et al, 2006). In guineagrass, many markers linked to the apomixis locus were obtained by bulked segregation analysis (Ebina et al, 2005).…”
Section: Genomic Studies Of Apomixismentioning
confidence: 99%